2007
DOI: 10.1089/end.2007.9904
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Pretreatment of Hydrogel Ureteral Stent

Abstract: Hydrogel coating on the surface of ureteral stents does not prevent or reduce bacterial adhesion. However, after antibiotic treatment, stents exhibit antibacterial activity in the local environment at greater intensity and for a longer time, depending on the bacterium-antibiotic combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Darouiche et al [34 ] found that urethral catheters soakedin chlorhexidine andprotaminesulphate were highlyresistant to biofilm formation in vitro and significantly resisted E. coli attachment in a rabbit model. Although it is not likely that this or other antibiotic-protamine sulphate combinations would prove valuable for long-term ureteral stenting, they could be beneficial for short-term stenting as well as for hydrating hydrogels [35] containing other longterm antibiofilm strategies, thus providing additional antimicrobial benefits.…”
Section: Biofilm Prevention and Treatment Strategiesmentioning
confidence: 99%
“…Darouiche et al [34 ] found that urethral catheters soakedin chlorhexidine andprotaminesulphate were highlyresistant to biofilm formation in vitro and significantly resisted E. coli attachment in a rabbit model. Although it is not likely that this or other antibiotic-protamine sulphate combinations would prove valuable for long-term ureteral stenting, they could be beneficial for short-term stenting as well as for hydrating hydrogels [35] containing other longterm antibiofilm strategies, thus providing additional antimicrobial benefits.…”
Section: Biofilm Prevention and Treatment Strategiesmentioning
confidence: 99%
“…Some strategies have used chemical approaches such as antiadhesins/polymeric coatings (Cassinelli et al 2000;van de Belt et al 2001;von Bismarck et al 2001;John et al 2007;Johansson et al 2008), quorum sensing inhibitors (Francolini et al 2004;Cirioni et al 2006;Antoniani et al 2010), biosynthesis inhibitors (Ueda et al 2009), biofilm dispersal agents (Raad et al 2007;Kim et al 2008;Barraud et al 2009;Cai et al 2009;Davies & Marques 2009) and natural products (Bjarnsholt et al 2007;Kalishwaralal et al 2010;Kostenko et al 2010;Wu et al 2011), among others. Physical methods have also been investigated, including ultrasound waves (Ensing et al 2005), low frequency vibrations (Bandara et al 2014) and other methods (Di Poto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ureteral stents made of an olefinic block copolymer were coated with a hydrogel that was subsequently impregnated with antibiotics [97]. These stents demonstrated in vitro antimicrobial activity for 3–16 days against common ureteral pathogens.…”
Section: Requirements For Local Antimicrobial Delivery Systems Andmentioning
confidence: 99%